Resistivity measurement of ZnO:AI films for solar cell - Tan, Hang Khume (2006)
Aluminium doped Zinc Oxide films were deposited on glass slide by RF magnetron sputtering using a ZnO target mixed with A120J. All the films were growth in room temperature without intentional heating. The resistivity of the ZnO:AI films were measured using van der Pauw method in terms of the preparation conditions such as RF power, working pressure, deposition time, O2 content in sputtering gas and target-substrate distance. Resistivity of the deposited films shows the following behaviours: decreases with the increasing RF power and film thickness while increase with increasing target substrate distance, and O2 content in sputtering gas. Resistivity for films prepared in different working pressure decreases with the Argon pressure but increased after the optimal pressure of 45mTorr.